Data visualization with python and Java script: scarpe, explore and transform your data - Dale, Kyran (Beijing, China : Shroff Publishers and Distributer Pvt. Ltd., 2023)
Data Visualization with Python and JavaScript by Kyran Dale is a comprehensive guide that empowers readers to transform raw, unprocessed data into dynamic, interactive web visualizations. The book effectively bridges the gap between data science and web development, leveraging the strengths of Python and JavaScript. It covers essential topics like data acquisition, cleaning, processing, and visualization. By providing practical examples and emphasizing best practices, Dale guides readers through the process of creating visually appealing and insightful data visualizations. Whether you're a data scientist, analyst, or developer, this book is an invaluable resource for mastering the art of data storytelling.
Includes index.
Keywords: Python for data manipulation and analysis; Javascript for interactive visualizations; Scraping data; Creating visualizations